Analysis Of The Character Of Discipline And Responsibility In Shaping The Morals Of Al-Karimah Students Of Sma Negeri 51 Kabupaten Maluku Tengah - Khozin, M.Pd.I, Nur (IAIN Ambon, 2023)
Abstract: The purpose of this study was to determine the character, discipline and responsibility of students of SMA Negeri 51 Kabupaten Maluku Tengah. This research is a descriptive quantitative research. Data collection using observation, interviews and documentation. Data analysis uses data reduction, data presentation, and conclusions. The results showed that in general, students of SMA Negeri 51 Kabupaten Maluku Tengah already have the character of discipline and responsibility, come to school on time, wear school uniforms with rules, obey school rules, do and collect assignments according to the specified time. However, there are still some students who have not applied these two characters, so schools need to apply discipline more strictly and teach the character of responsibility so that they can become students with morals.